Getting the Dog to Bark : Disclosing Fiscal Risks from the Financial Sector - Irwin, Timothy (IMF Working Papers; Working Paper ;, 2015)
Fiscal reporting is intended to warn of fiscal crises while there is still time to prevent them. The recent crisis thus seems to reveal a failure of fiscal reporting: before the crisis, even reports on fiscal risk typically did not mention banks as a possible source of fiscal problems. One reason for silence was that the risk arose partly from implicit guarantees, and governments may have feared that disclosure would increase moral hazard. The crisis cast doubt, however, on the effectiveness of silence in mitigating risks. This paper discusses how fiscal risks from the financial sector could be discussed in reports on fiscal risk, with a view to encouraging their mitigation.